Penyiangan bahan pustaka di Perpustakaan Cinta Baca Palembang - Marina Marina (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2022)
This article focuses on weeding the collection at the Cinta Baca Library in Palembang. The aims of this study were to (1) Find out how to weed library materials at the Cinta Baca Library in Palembang; (2) Obstacles faced by the Palembang Reading Love Library in weeding library materials. Descriptive analysis of the data, by analyzing the data we can conclude that: First, the process of weeding library materials at the Palembang Cinta Baca Library has not been effective and the activity is still limited to separating collections or library materials. Second, the obstacle faced by the Cinta Baca Library in Palembang in weeding library materials is the absence of written guidelines for weeding from the Center, namely the Cinta Baca Library, Bogor.